Bush y el millennium challenge account: ¿a favor o contra los pobres? - Illán Sailer, Carlos (Revista Española de Desarrollo y Cooperación, 2023)
The article offers an updated review of the Millennium Challenge Account (MCA), the Aid program launched by president Bush in march 2002, while it also tries to shed some light on the prospects of this iniciative in an international context where security and the politization of aid seem to have become a priority on the donors agenda.